Viral Inhibitory Peptide of TLR4, a Peptide Derived from Vaccinia Protein A46, Specifically Inhibits TLR4 by Directly Targeting MyD88 Adaptor-Like and TRIF-Related Adaptor Molecule - BOWIE, ANDREW (My University, 2010)
TLRs are critical pattern recognition receptors, which recognize bacterial and viral pathogen associated molecular patterns leading to innate and adaptive immune responses. TLRs signal via homotypic interactions between their cytoplasmic Toll-IL- 1 receptor (TIR) domains and TIR domain-containing adaptor proteins. Over the course of evolution viruses have developed various immune evasion strategies, one of which involves inhibiting TLR signaling pathways in order to avoid immune detection. Thus, vaccinia virus (VACV) encodes the A46 protein, which binds to multiple TIR-domain containing proteins, ultimately preventing TLRs from signaling. We have identified an 11-amino acid long peptide from A46 (termed VIPER), which when fused to a cell-penetrating delivery sequence potently inhibits TLR4-mediated responses. VIPER was TLR4-specific, being inert towards other TLR pathways, and was active in murine and human cells and in vivo, where it inhibited LPS-induced IL- 12p40 secretion. VIPER also prevented TLR4-mediated MAPK and transcription factor activation, suggesting it acted close to the TLR4 complex. Indeed, VIPER directly interacted with the TLR4 adaptor proteins Mal and TRAM. Viral proteins target host proteins using evolutionary optimized binding surfaces. Thus VIPER possibly represents a surface domain of A46 that specifically inhibits TLR4 by masking critical binding sites on Mal and TRAM. Apart from its potential therapeutic and experimental use in suppressing TLR4 function, identification of VIPER's specific binding sites on TRAM and Mal may reveal novel therapeutic target sites. Overall, we demonstrate for the first time disruption of a specific TLR signaling pathway by a short virally-derived peptide.
PUBLISHED
Keywords: TLR4; Immunology, Inflammation & Infection